Analisis Data untuk Memprediksi Pagu Minus dan Membantu PPK dalam Pelaksanaan Pengujian Material - Ida Puspita Ningtias; Julianda Rosyadi; Wawan Hadinata; Agustina Diprianti; Anung Faizal Hanani Wijaya (Jurnal Manajemen Perbendaharaan, 2022)
Budget availability and fairness of billing are things that had to be assured by Pejabat Pembuat Komitmen (PPK) or Commitment Making Official before paying a bill with the state budget. Analyzing the data in Platform Pembayaran Pemerintah (PPP) or Government Payment Platform could help PPK to predict the budget availability and fairness of billing. PPP is an interconnection between the core system, support system, partner system, and monitoring system. This interconnection enables more reliable data collection because there is a data exchange within the ecosystem, such as the electricity bills. The data would be analyzed to predict the occurrence of shortfalls and to evaluate the billing fairness. For the prediction of the occurrence of shortfalls, clustered time series forecasting is used with the ARIMA model, while to assist in the fair assessment of billing, descriptive statistics of historical data are used to evaluate the current bills. From the results of the analysis, it can be seen that the ARIMA model can be used to predict the occurrence of a budget shortfall and descriptive statistics can be used as a basis for evaluating current bills.